Eggs Are Cost-Efficient in Delivering Several Shortfall Nutrients in the American Diet: A Cost-Analysis in Children and Adults - Papanikolaou, Yanni (Nutrients, 2020)
The purpose of the current study was to examine the cost of eggs in relation to nutrient delivery in children and adults. The present analysis used dietary intake data from the National Health and Nutrition Examination Survey 2013–2016 (egg consumers: 2–18 years-old, N = 956; 19+ years-old, N = 2424). Inflation adjusted food cost and the cost of nutrients were obtained from the Center for Nutrition Promotion and Policy food cost database. Cost and nutrient profiles for What We Eat in America food categories were compared to whole eggs. Of the 15 main food groups examined, whole eggs ranked third for lowest cost per 100 g (excluding beverages), such that eggs cost 0.35 USD per 100 g, with dairy and grains representing the first and second most cost-efficient foods, at 0.23 USD and 0.27 USD per 100 g, respectively. In children and adults, eggs represented a cost-efficient food for protein delivery, such that eggs provided nearly 2.7% and 3.7% of all protein in the diet, respectively, at a cost of about 0.03 USD per g of protein. Eggs contributed 3.8% and 6.0% of all vitamin A in the diet of children and adults, at a cost of approximately 0.002 USD and 0.003 USD per RAE mcg of vitamin A, respectively. In children 2–18 years-old, nearly 12% of all choline in the diet is delivered from eggs, at a cost of approximately 0.002 USD per mg of choline. Similarly, in adults 19-years-old+, eggs provide nearly 15% of all dietary choline in the diet, at a cost of approximately 0.002 USD per mg of choline. Eggs provide nearly 5% and 9.5% of all vitamin D in the diet of children and adults, at a cost of approximately 0.21 USD and 0.22 USD per mcg of vitamin D, respectively. Overall, eggs ranked as the most cost-efficient food for delivering protein, choline, and vitamin A, second for vitamin E, and third for vitamin D in children. In adults, eggs ranked as the most cost-efficient food for delivering protein and choline, second for vitamin A, and third for vitamin D and vitamin E. In summary, eggs represent an economical food choice for the delivery of protein and several shortfall nutrients (choline, vitamin A, and vitamin D) in the American diet.